A proposal for a tourism regionalization of Poland based on the highest levels of tourism in a region - Sobotka, Sławomir (Turyzm/Tourism, 2014)
The paper presents a brief review of twenty proposals for tourism regionalization of either a part of or the whole of Poland (or attempts to delimit the most attractive areas in terms of leisure), formulated between 1938 and 2012. It also analyses selected definitions of tourism regions and discusses the indicators which are proposed for the delimitation of tourism regions. Moreover, the paper attempts to indicate areas with the highest levels of tourism, in part modelled on Maria Mileska (1908-1988). It includes academic (precise) criteria for the designation of tourism regions. Some researchers’ comment that Mileska’s work is (partially) outmoded not so much from the methods employed as in the number of tourism regions and the areas covered. This should be regarded as understandable given that this regionalization was formulated at the beginning of the 1960s. Another important issue raised is the most recent tourism regionalization of Poland as prepared by Durydiwka.